Controlled Pinning of Conjugated Polymer Spherulites and Its Application in Detectors. Issue 19 (31st July 2017) - Dörling, Bernhard; Sánchez‐Díaz, Antonio; Arteaga, Oriol; Veciana, Andrea; Alonso, Maria Isabel; Campoy‐Quiles, Mariano
Abstract : The nucleation of single macroscopic spherulites at desired positions, as well as ordered arrays of multiple spherulites, is demonstrated by combining the use of crystallizable solvents with local control of solvent evaporation during solution deposition. Moreover, the temperature assisted localized frustration of molecular orientation is shown, enabling the fabrication of samples containing both isotropic areas and spherulites. These macroscopic circular polycrystalline structures are characterized using a range of polarized spectroscopic techniques that allow quantifying their large degree of chain orientation. In order to show the potential of these large conjugated polymer spherulites centered at desired locations, graded bilayer organic photovoltaic devices were fabricated to be used as polarimeters, solid state light polarization detectors with no moving parts, and position sensitive photodetectors. Abstract : The localization of macroscopic spherulites at desired positions directly from solution is presented. These polycrystalline structures of densely branched, circularly radiating conjugated polymer fibers are obtained by controlling the solvent evaporation of a solution containing a crystallizable solvent additive. Single spherulites, as well as ordered arrays are demonstrated, together with their applications as polarization sensitive photodetectors.